PROGRAM OF MAKING ORGANIC PESTICIDES ON THE MEUGAH RAYA WOMEN'S FARMER GROUP AND RASEUKI SEUMULA WOMEN'S FARMER GROUP IN UTARA ACEH - Tambarta, Emmia; Ramayana, Ramayana; Romano, Romano; Fadli, Fadli; Ahmad Syahwier, Coki; Nura, Nura (RADJA PUBLIKA, 2022)
Using pesticides is familiar to farmers, especially in North Aceh Regency. But the use of chemical pesticides continuously is not recommended because it have negative impacts such as increasing pest resistance, the emergence of new pests, killing the natural enemies/predators, buildup of chemical residues in crops and causing environmental pollution. Pesticides are chemical substances and other substances which use to control various pests. For farmers, the types of pests are mites, nuisance plants, plant diseases caused by fungi (fungi), bacteria, viruses, nematodes (worms that damage roots), snails, rats, birds and other animals that are considered harmful to the corps. The sustainable use of chemical pesticides will certainly damage the environment so that it can harm rural communities who generally work as farmers. The best solution is to produce organic pesticides independently with ingredients that are easily available in the surrounding environment. Therefore, State Universities in Sumatra collaborate with Corporate Social responsibility PT. Pupuk Iskandar Muda (CSR PT. PIM) as a partner of DUDI (Industrial Side) also contributed to solving this problem by implementing a training program for making organic pesticides for the women's farmer group Meugah Raya and the Raseuki Seumula farmer group in North Aceh.